Dynamic and non-contact 3D sample rotation for microscopy. Issue 1 (December 2018) - Berndt, Frederic; Shah, Gopi; Power, Rory; Brugués, Jan; Huisken, Jan
Abstract Precise sample orientation is crucial for microscopy but is often performed with macroscopic tools and low accuracy. In vivo imaging of growing and developing samples even requires dynamic adaptation of the sample orientation to continuously achieve optimal imaging. Here, we present a method for freely positioning a sample in 3D by introducing magnetic beads and applying a magnetic field. We demonstrate magnetic orientation of fixed mouse embryos andartemia, and live zebrafish embryos and larvae on an epi-fluorescence microscope and on a light-sheet system for optimal imaging. Sample orientation is crucial to ensure optimal image quality in light microscopy. Here the authors enable multi-axis orientation of fixed mouse embryos and shrimp, and live zebrafish embryos and larvae by introducing magnetic beads and rotating the sample with a magnetic field in a microscope.